INFLASI, PERTUMBUHAN PENJUALAN, DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR HEALTHCARE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Sari, Ferina; Situmorang, Christina Verawati (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2025)
This study aims to analyze the effect of inflation, sales growth, and profitability on stock prices in healthcare sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach was used with multiple linear regression analysis. The sample was selected using a purposive sampling technique, comprising 17 companies that were consistently listed on the IDX throughout the five-year observation period, resulting in 85 observation units. The data used are secondary data obtained from company financial statements published on the official IDX website (www.idx.co.id). Data analysis was conducted using SPSS version 25, which included descriptive statistics, classical assumption tests, and hypothesis testing through the adjusted coefficient of determination (Adjusted R²), t-test, and F-test. The results show that simultaneously, the variables inflation, sales growth, and profitability (measured by Return on Equity/ROE) significantly affect stock prices, with an adjusted R² value of 34.3%. However, partially, inflation and sales growth do not have a significant effect on stock prices, while ROE has a significant influence. These findings indicate that although inflation and sales growth are not yet the main determinants of stock price increases, ROE remains the key indicator most considered by investors. The implication of these findings suggests that companies should not only focus on increasing profitability but also actively manage inflation risk and optimize sales growth as part of their stock value enhancement strategy. Although the impact of inflation and sales growth is not statistically significant, consistent management of these factors remains essential as it can shape positive investor perceptions, ultimately contributing to long-term stock price stability and growth, especially amid increasing market expectations for sustainable and responsible business practices.